(untitled) (Journal of Science and Technology, 2016)
The population growth in Ghana has been a matter of great concern. Resources are inadequate to cater for the growing population. The demographic variable that chiefly accounts for the growth is fertility. The research examines the factors that inhibit the regulation of fertility in Ghana. Tien districts, Kumasi Metropolis representing urban areas in the country, and Kwabre-Sekyere representing rural areas, were the selected areas for study. Literature on the theme in other areas of Ghana war reviewed to buttress the findings. The sources of data were books on fertility, surveys on fertility and population and vital statistics report, of the United Nations, Personal Interview was the. main research instrument, supplemented by a few questionnaire schedules. A total sample size of 168 females was used apart from a sample of416 by other researchers. The selection was made through stratification. Data were analysed with the statistical techniques of percentages, proportions and classifications The study revealed that, the greatest hindrances to fertility regulation in Ghana are illiteracy and traditionalism There is the need for pragmatic steps by the governmental and non-governmental organizations to reverse the trend, else, the population problem will continue to haunt efforts at socio-economic development.